CYBERSECURITY LESSONS FROM COVID-19. - Slade, Robert ([Place of publication not identified] : CRC PRESS, 2021)
Using the SARS-CoV-2/CoVID-19 pandemic as a giant case study, and following the structure of the domains of information security, this book looks at what the crisis teaches us about security. It points out specific security fundamentals where social, medical, or business responses to the crisis failed or needed to make specific use of those concepts. For the most part, these lessons are simply reminders of factors that get neglected during times of non-crisis. The lessons particularly point out the importance of planning and resilience in systems and business. Those studying cybersecurity and its preventive measures and applications, as well as those involved in risk management studies and assessments, will all benefit greatly from the book. Robert Slade has had an extensive and prolific career in management, security, and telecommunications research, analysis, and consultancy. He has served as an educator visiting universities and delivering lecturers and seminars.
OCLC-licensed vendor bibliographic record.
Keywords: Computer security; Computer crimes -- Prevention; COMPUTERS / Disaster Recovery; COMPUTERS / Security / General; MATHEMATICS / General